PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB (MUFRADAT) MELALUI PENGGUNAAN MEDIA KARTU KATA BERGAMBAR - FAJRIAH, ZAHRATUN (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The purpose of this study was to describe the process and learning outcomes using pictorial word card media can enhance vocabulary mastery of Arabic (mufradat) students in grade I MI Nurul Hakim Kediri West Lombok in 2015 with research subjects are 19 students. The data analysis technique used is the analysis of qualitative and quantitative data. Qualitative data analysis is used to collect data through field notes, observation sheet, interview notes, and notes dokumentasi.Analisis quantitative data used to determine the percentage increase in the mastery of Arabic vocabulary (mufradat) after the action using the word picture card media. The results showed an increase in students' mastery of Arabic vocabulary using word picture card media. In the first cycle, obtained an increase of 52.17% and increased to 81.56% in the second cycle. Based on the quantitative data that is reinforced by the findings of qualitative data that use the media card can increase the procurement of said picture koasakata Arabic (mufradat). Keywords: Mastery of Arabic Vocabularies, Picture Cards, Action Research